A Simple-to-Implement Simulator for the Reactive Extrusion of Poly(Lactic Acid) in a Corotating Uniform Twin-Screw Extruder - René O. Vargas; J. Esteban López-Aguilar; Lorenzo A. Martínez-Suástegui; Francisco López-Serrano (Advances in Materials Science and Engineering)
The present paper deals with the poly(lactic acid) (PLA) reactive processing simulation in a uniform corotating twin-screw extruder that can be readily turned into practical applications in pilot and industrial equipment. The simulator provides a cause-effect guide that can be useful for starting an experimental setup in a reactive screw extruder for a biopolymer in a growing industry. The proposed model considers a free radical ring-opening mechanism involving the main characteristic flows inside the extruder and the non-Newtonian behavior of PLA. The characteristic behavior relating reaction rate, average molecular weights, and polydispersity against chamber number are described by S-shaped and monotonically decreasing curves, for the equipment. Numerical predictions show that this simple and easy to implement model accurately reproduces previously reported data and that the impurity concentration exhibits a marked effect over all the variables, except conversion.